Cutting the ribbon: bathyal Nemertea from seeps along the Costa Rica margin, with descriptions of 2 new genera and 9 new species - Sagorny, Christina; Döhren, Jörn von; Rouse, Greg W.; Tilic, Ekin (European Journal of Taxonomy, 2022)
The taxonomy of ribbon worms (Nemertea) is particularly challenging due to the sparsity of distinct morphological characters, causing a significant underestimation of the group’s true diversity. The number of named deep-sea species is very limited and there is a vast number of undescribed deep-sea nemerteans still to be discovered. In this paper we figuratively ‘cut the ribbon’ and name seven new species of monostiliferous hoplonemerteans from seeps and seamounts along the Costa Rican margin, one from seeps along the Oregon margin, and one from vents of the Juan de Fuca Ridge, USA. The species Chernyshevia escarpiaphila gen. et sp. nov. and five species of the genus Alvinonemertes gen. nov. (Alvinonemertes dariae gen. et sp. nov., Alvinonemertes dagmarae gen. et sp. nov., Alvinonemertes christianeae gen. et sp. nov., Alvinonemertes claudiae gen. et sp. nov., Alvinonemertes tatjanae gen. et sp. nov.) represent Oerstediina, whereas the three species Tetrastemma sundbergi sp. nov., Tetrastemma polyakovae sp. nov., and Tetrastemma strandae sp. nov. represent Amphiporina. One species of tubulanid palaeonemerteans is described but not provided with a species name due to lacking sequence data for comparison. Additionally, we provide sequence data for one lineid heteronemertean, one reptant hoplonemertean, and two further eumonostiliferan hoplonemertean species. We use an integrative, turbotaxonomic approach combining DNA sequence data with concise morphological descriptions and fully digitized serial histological sections made available as cybertypes.